Specialization in Sociology - Reviandy Azhar Ramdhani; Rokibullah Rokibullah; Devi Yulia (Pelopor Publikasi Akademika, 2022)
In general, Sociology focuses and focuses on studies related to something related to human behavior in society. However, sociology in essence or in general has a different or diverse approach in viewing the objects contained in sociology. There are sociologists who view and are more interested in discussing deviant behavior in individual humans and society or criminal sociology, many also review sociology in the political field which is based on people's behavior. This article is researched through a qualitative descriptive method as a reference. The purpose of this article is to make us know what sociology is, so that we know various kinds of things that are related and contained in sociology, and so that we know the reciprocity between sociology and various other sciences.